Effects of the Encapsulating Membranes on the Translations of Pairs of Non-spherical Bubbles. (November 2015) - Liu, Yunqiao; Sugiyama, Kazuyasu; Takagi, Shu
Abstract: In this paper, we perform a theoretical analysis on the translational motions ofgas and encapsulated bubbles undergoing deformation. We verify our theoretical model for the case of a gas bubble collapsing near a wall. By comparison, the encapsulated bubble near the wall is less unstable in shape. In the second case, the translations of two gas bubbles subjected to an oscillating driving pressure agree with Bjerknes' theory, that is, the two bubbles repel each other when the driving frequency is between the two natural frequencies ω01 < ω d < ω02 ; while the two bubbles move towards each other at ω d < ω01 or ω d > ω02 . For encapsulated bubbles, the translational displacements are smaller than those of gas bubbles. The encapsulating membrane and the deformation affect the translational direction. The encapsulated bubbles are prone to experience repulsive motion at resonance.